Production of salidroside in metabolically engineered Escherichia coli - Bai, Yanfen (Nature Publishing Group, 2014)
Salidroside (1) is the most important bioactive component of Rhodiola (also called as “Tibetan Ginseng”), which is a valuable medicinal herb exhibiting several adaptogenic properties. Due to the inefficiency of plant extraction and chemical synthesis, the supply of salidroside (1) is currently limited. Herein, we achieved unprecedented biosynthesis of salidroside (1) from glucose in a microorganism. First, the pyruvate decarboxylase ARO10 and endogenous alcohol dehydrogenases were recruited to convert 4-hydroxyphenylpyruvate (2), an intermediate of L-tyrosine pathway, to tyrosol (3) in Escherichia coli. Subsequently, tyrosol production was improved by overexpressing the pathway genes, and by eliminating competing pathways and feedback inhibition. Finally, by introducing Rhodiola-derived glycosyltransferase UGT73B6 into the above-mentioned recombinant strain, salidroside (1) was produced with a titer of 56.9 mg/L. Interestingly, the Rhodiola-derived glycosyltransferase, UGT73B6, also catalyzed the attachment of glucose to the phenol position of tyrosol (3) to form icariside D2 (4), which was not reported in any previous literatures.